Experimental and numerical investigation of heat loss in transition modes of buried hot fuel oil pipeline. (November 2021) - Dehdarinejad, Mohsen; Behbahani-Nejad, Morteza; Hajidavalloo, Ebrahim
In this research, heat transfer of fuel oil flow through the buried pipeline in three regimes, turbulent, transition, and laminar conditions are investigated. A large-scale laboratory set-up is designed for this purpose and numerical modeling was also performed to study the effect of different parameters. The simulation is based on the fluid's thermophysical properties and the results are validated using experimental data. Due to the strong dependence of viscosity and density of fuel oil on the temperature, regime changes along the pipeline happens which complicate the calculation of friction factor. Using the experiment results and choosing different numerical methods, the acceptable model of friction factor in the transition zone for the experimental pipe and the real pipeline was achieved. Numerical simulation was performed on a 107 km pipeline using a powerful computer network to achieve the results. The approach which is used to simulate laminarization shows just a 3% discrepancy with experimental data. For the real pipeline, about 30 percent of the length is in transition mode from turbulent to laminar. The diameter of 26" is chosen as the most optimal size to transform 180000 barrels per day (BPD). According to the design thickness, diameter, and length of the pipeline, the maximum safe stop time (MSST) of the pipeline is 41 hours which is the most important data in the pipeline's maintenance period. Based on the present experimental data and simulation results, the optimal depth for the least heat loss from this pipeline is 0.9 to 2.7 meters.